Innovation management in research incubators at public universities (CONOCIMIENTO, INVESTIGACIÓN Y EDUCACIÓN CIE, 2018)
The purpose of this article is to reveal the results of innovation management in the research seedbeds of public universities in the Department of Cesar. The methodology was based on a quantitative descriptive approach, with field characteristics and a non-experimental, cross-sectional design. The population consisted of research seedbed directors and vice-rectors for research, with a sample of 39 individuals. An instrument with 30 items was constructed, using a five-point Likert scale. The results showed the current state of innovation management in the research seedbeds and led to conclusions that may be useful for improving it.